Development of consumer complaints regimes in Malaysia and Japan - Morinaga, Daisaku; Mat Said, Aini (Persatuan Ekonomi Pengguna dan Keluarga Malaysia (MACFEA), 2012)
The number of consumer complaints is expected to increase in concert with the rising awareness of consumer rights and accessibility to consumer complaint bureaus. A review of consumer complaint reports published by various consumer complaint agencies in Malaysia and Japan was carried out to gauge the trend in consumer complaints behaviour. Data indicates that the number of complaints is on the increase and that service failures outweighed product quality grievances for both Japan and Malaysia. The Malaysian consumers used multiple channels to lodge their complaints but internet is fast becoming the dominant mode. Dispute resolution systems in both countries are compared and discussed. Ways of enhancing consumer complaint management system is proposed as consumers are presently overwhelmed with both extensive range of product choices and widening gaps in the quality.